2021
DOI: 10.1186/s13643-020-01574-5
|View full text |Cite
|
Sign up to set email alerts
|

Global concerns of dental and oral health workers during COVID-19 outbreak: a scope study on the concerns and the coping strategies

Abstract: Background Dental and oral health workers have direct contact with respiratory aerosols of patients during procedures. This study aimed to determine the main concerns of dental and oral health workers globally during COVID-19 outbreaks and the coping strategies that help the resilience of dental and oral healthcare system. Methods This scoping study was conducted in August 2020. After adjusting the search strategy, a systematic search of five datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 55 publications
1
28
0
2
Order By: Relevance
“…Just over half (52%) of the participants felt that external factors controlled their life, while a similar percentage (54.6%) agreed that they were in control of protecting themselves. This study also found that the majority of participants were stressed about the COVID-19 situation, which was similar to the findings by León-Manco et al 2021 [32] and Bastani et al 2021 [33]. Although they were stressed, most participants of this study had social support systems and mechanisms to deal with the stress, which mainly involved calling friends and colleagues over phone/video calls and engaging in hobbies.…”
Section: Discussionsupporting
confidence: 88%
“…Just over half (52%) of the participants felt that external factors controlled their life, while a similar percentage (54.6%) agreed that they were in control of protecting themselves. This study also found that the majority of participants were stressed about the COVID-19 situation, which was similar to the findings by León-Manco et al 2021 [32] and Bastani et al 2021 [33]. Although they were stressed, most participants of this study had social support systems and mechanisms to deal with the stress, which mainly involved calling friends and colleagues over phone/video calls and engaging in hobbies.…”
Section: Discussionsupporting
confidence: 88%
“… 50 , 51 , 52 , 53 , 54 Additionally, financial hardships associated with concerns about losing their job or loss of earning in the practice as well as unexpected investments in infection control procedures have been reported as triggers of financial stress. 55 , 56 Jungo et al, reported that dentists in France were more concerned about the financial viability of their practice than they were about being infected with the virus. 57 Despite reporting being stressed at work, over half of the respondents indicated that they did not have debriefing or psychological support services at their workplace.…”
Section: Discussionmentioning
confidence: 99%
“…The wide geographical distribution and the representation of the public and private healthcare settings minimised the possible bias in the resulting data; however, these results cannot be extrapolated to the country as a whole. This methodology (i.e., via social networks) [24,26,28] was chosen because it allows faster and broader access to the intended populations. Some of the main concerns for oral health professionals after the coronavirus outbreak were the economic repercussions that the closure or reduction of the number of patients in dental centres caused [29,30], the increases in costs, and the difficulty in acquiring PPE, in addition to new investments in resources or infrastructures [30,31].…”
Section: Discussionmentioning
confidence: 99%